Kajian daya dukung perairan Danau Bulilin, Tombatu, Minahasa Tenggara, untuk akuakultur dengan parameter [P] - Frandy Ombong; Indra Raymond Nicolas Salindeho (Universitas Sam Ratulangi, 2023)
The research were aimed to assess the carrying capacity of the Bulilin Lake waters, to ensure a sustainable aquacutural production. The research was carried out from September to Desember 2016. The carrying capacity of the Bulilin lake was assessed using the method developed by Beveridge (2004), where several parameters of water quality, aquacultural production, and the physical condition of the lake such as, the dimensions of the lake, flushing rate, total phosphate [P], total aquacultural production per year and Food Conversion Ratio (FCR), were required in the assessment. Collected data were, then, analyzed using the procedures of calculation, which were combined with the several assumptions and modeling based on the previous research. Water samples for phosphate [P] analysis were collected from 6 different points on the surface and and at a depth of three meters, representing the overall water condition of the lake. Aquacultural protocols and production data were collected using questionnaires and by direct observation at the farm. The result shows that the area of Bulilin Lake is around ± 244,562 m2, with an average depth of 3.11 meters. The phosphate [P] content ranged from 0.0263 mg/L to 0.0843 mg/L, with an average of 0.0490 mg/L, which is still below the maximum recommended value for waters used for aquacultural production. Flushing rate value of Bulilin lake waters was as high as 6.479 per year, meaning that there was a total water exchange of Bulilin lake in every 2 months. Total aquacultural production per year in Bulilin Lake was estimated around 268,959 tonnes of fish per year, which was below the carrying capacity of the waters of the Bulilin Lake. In conclusion, the total production for the coming year could be increased as many as 92.12 tonnes per year, provided that sustainable culture technology is applied. Keywords: Bulilin, ortophosphate, carrying-capacity, aquaculture